Membrane domain formation—a key factor for targeted intracellular drug delivery - Popov-Čeleketić, Dušan; van Bergen en Henegouwen, Paul M. P. (Frontiers in Physiology, 2014)
Protein molecules, toxins and viruses internalize into the cell via receptor-mediated endocytosis (RME) using specific proteins and lipids in the plasma membrane. The plasma membrane is a barrier for many pharmaceutical agents to enter into the cytoplasm of target cells. In the case of cancer cells, tissue-specific biomarkers in the plasma membrane, like cancer-specific growth factor receptors, could be excellent candidates for RME-dependent drug delivery. Recent data suggest that agent binding to these receptors at the cell surface, resulting in membrane domain formation by receptor clustering, can be used for the initiation of RME. As a result, these pharmaceutical agents are internalized into the cells and follow different routes until they reach their final intracellular targets like lysosomes or Golgi. We propose that clustering induced formation of plasma membrane microdomains enriched in receptors, sphingolipids, and inositol lipids, leads to membrane bending which functions as the onset of RME. In this review we will focus on the role of domain formation in RME and discuss potential applications for targeted intracellular drug delivery.